Are condition factors powerful proxies of energy content in wild tropical tunas?. (December 2016) - Sardenne, Fany; Chassot, Emmanuel; Fouché, Edwin; Ménard, Frédéric; Lucas, Vincent; Bodin, Nathalie
Abstract: The "condition" is used as an indicator of fish health and is generally equated with the quantity of energy reserves. Biometric condition factors have been widely used and preferred over costly and time-consuming biochemical condition. Here, we investigated the relevance of four common condition factors based on biometric measurements (Le Cren's index, girth-length index, gonado-somatic index and hepato-somatic index) and of size- and weight-based empirical models to describe the physiological condition of tropical tunas. Biometric condition factors of bigeye ( Thunnus obesus ), skipjack ( Katsuwonus pelamis ) and yellowfin ( Thunnus albacares ) tunas sampled throughout 2013 in the western Indian Ocean region were assessed against benchmark biochemical indices (lipid content, protein content, triacylglycerol:sterol ratio and energy density) estimated in tissues with different physiological functions, i.e. red muscle, white muscle, liver, and gonads. Our findings suggest that tropical tunas do not store lipids in white muscle and that protein content is less variable than lipid content, which largely varies with ontogeny and the seasons according to tissue and species. This variability induced inconsistency between biometric factors, including the empirically adjusted ones, and biochemical indices, with the exception of the gonado-somatic index that fitted well to the composition of the gonads in the three species, and especially in females.